2022
DOI: 10.3389/fonc.2022.796263
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Mutational Burden Associated With Response to Hyperthermic Intraperitoneal Chemotherapy

Abstract: BackgroundGastric cancer (GC) is one of the most common cancer types, especially in Asian countries. Hyperthermic intraperitoneal chemotherapy (HIPEC) has been shown to improve the progression-free survival among gastric cancer patients with peritoneal metastases; however, not all patients demonstrate response to HIPEC.MethodsBiomarkers are needed to select patients for effective treatment of HIPEC. Here, we performed whole-exome sequencing on tumor samples from 18 gastric cancer patients who received HIPEC tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Our results indicated that TMB was higher in non-responders than that in responders, which is consistent with a previous finding of colorectal PM treated with CRS/HIPEC ( 48 ). Conversely, the correlation between high TMB and better responses to HIPEC was reported in gastric PM patients ( 49 ). The inconsistent results might be due to the tumor heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that TMB was higher in non-responders than that in responders, which is consistent with a previous finding of colorectal PM treated with CRS/HIPEC ( 48 ). Conversely, the correlation between high TMB and better responses to HIPEC was reported in gastric PM patients ( 49 ). The inconsistent results might be due to the tumor heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Standard molecular analysis should be conducted, which includes assessing for microsatellite instability (MSI), RAS mutations (KRAS, NRAS, and HRAS), BRAF mutations, ERBB2 (formerly HER2) status, and tumor mutational burden (TMB) by next-generation sequencing (NGS) [31] [32]. NGS also has the potential to identify sequence variations, such as ERBB2 amplifications or NTRK gene fusions [33].…”
Section: Block 1: Initial Management and Preoperative Considerationsmentioning
confidence: 99%